(untitled) (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2012)
In this paper we propose a model of preferences based on reciprocity. This model allows us to explain the cooperative behavior that exists within any business organization.We try to show that, opposite to more conventional literature, the optimal behavior is the cooperation among team members.